2023
DOI: 10.3389/fnagi.2022.1072003
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome is a potential mechanism and therapeutic target for perioperative neurocognitive disorders

Abstract: Perioperative neurocognitive disorders (PNDs) are frequent complications associated with cognitive impairment during the perioperative period, including acute postoperative delirium and long-lasting postoperative cognitive dysfunction. There are some risk factors for PNDs, such as age, surgical trauma, anesthetics, and the health of the patient, but the underlying mechanism has not been fully elucidated. Pyroptosis is a form of programmed cell death that is mediated by the gasdermin protein and is involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Reproduced with permission. [ 203 ] Copyright 2020, ACS publication. d) Illustration (α) of NIR‐II‐excited catalyst inhibiting Aβ aggregation by photooxygenation; (β) TEM images of Aβ42, and Aβ42+DSM@n‐HOF‐6+NIR‐II; (γ) Representative swimming paths of mice in different groups.…”
Section: Pd Approaches: Nanomedicines For Treating Anesthesia‐related...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 203 ] Copyright 2020, ACS publication. d) Illustration (α) of NIR‐II‐excited catalyst inhibiting Aβ aggregation by photooxygenation; (β) TEM images of Aβ42, and Aβ42+DSM@n‐HOF‐6+NIR‐II; (γ) Representative swimming paths of mice in different groups.…”
Section: Pd Approaches: Nanomedicines For Treating Anesthesia‐related...mentioning
confidence: 99%
“…Scale bars: 300 nm; (𝛾) Representative swimming paths of mice in the probe test. Reproduced with permission [203]. Copyright 2020, ACS publication.…”
mentioning
confidence: 99%
“…Specifically, the NLRP3 inflammasome is present in microglial cells, while neurons contain the NLRP1 and AIM2 inflammasomes, and astrocytes harbor the NLRP2 inflammasome ( Wang M et al, 2022 ; Wang XF et al, 2022 ). The NLRP3 inflammasome, comprising the NLRP3 protein, pro-caspase-1, and apoptosis-associated speck-like protein containing a CARD (ASC), mediates neuroinflammation that not only directly contributes to the POCD but is also closely associated with high-risk factors for POCD ( Li et al, 2022 ). NLRP3 inflammasome activation occurs in two steps: initiation and activation ( Zhang et al, 2023 ).…”
Section: Biological Mechanism Of Electroacupuncture For Postoperative...mentioning
confidence: 99%
“…Previous clinical and animal studies have shown that surgery and anesthesia-induced acute peripheral inflammation and neuroinflammation may lead to delirium after surgery. 13,14 Mounting evidence has shown that inflammatory markers including elevated neutrophil, monocyte and reduced lymphocyte count, have been reported in various clinical setting. [15][16][17] Indeed, elevated neutrophil and reduced lymphocyte count has also reported in delirium in older adults.…”
Section: Introductionmentioning
confidence: 99%